Best practices in urban solid waste management : ownership, governance, and drivers of performance in a zero waste framework - Romano, Giulia; Marciano, Claudio; Fiorelli, Maria Silvia (Emerald points., 2021)
Efficient waste management is crucial for a sustainable future. However, due to population growth and the threat of global climate change, systems of urban waste management are under increasing pressure. For the waste sector, the prospect of transitioning to a circular economy presents an opportunity to promote organizational changes and improve performance, as well as contribute to a more sustainable world. Through the examination of case studies of municipalities and waste management firms across Europe, this book provides an overview of the most innovative best practices in urban waste management. The authors analyze the development and results of collection methods, tariff-setting systems, collaborations with partners and providers, recycling policies, and employees' and stakeholders' engagement programs. Given the complexity of urban waste management procedures, analysis is multidisciplinary, encompassing management, environmental and sociological perspectives. Providing an overview of opportunities for knowledge sharing and transfer among firms and municipalities to help them promote best practice, this book is a valuable reference for managers and policy makers in urban waste management.